Determination of bioactive compounds obtained by the green extraction of taioba leaves (Xanthosoma taioba) on hydrothermal processing - SANTOS,Orquídea Vasconcelos dos (2022)
Abstract The objective of this study was to obtain and characterize a freeze-dried powder of taioba leaves (Xanthosoma taioba) as a source of bioactive substances and potential food applications. The fresh leaves were cooked and lyophilized for further analysis. Its bioactive contents expressed in flavonoids, ascorbic acid and total polyphenols were quantified. Total antioxidant activity (TAA) was determined by ABTS assays. The chemical composition via infrared spectroscopy (FTIR) and its microstructure were visualized by scanning electron microscopy (SEM). The bioactive contents of flavonoids, ascorbic acid and polyphenols were 17.15 mg/100 g, 58.3 mg/100 g and 24.15 mg Eq. of gallic acid/100 g, respectively. A high content of TAA was found. ABTS 37.35 (µg TE/g). The FTIR spectrum revealed high-intensity bands at 3350 cm-1, 2928 cm-1, 1637 cm-1, and 1055 cm-1 related to vibrations associated with typical bands of −OH groups present in cellulose membranes, hemicellulose, carbohydrates, lignin and water. The micrographs showed irregular structures of the ground leaves with a fibrous structure. These results indicate a high potential of this raw material in food formulations as a source of bioactives suitable for applications in various industrial segments.